2017
DOI: 10.1371/journal.pone.0180712
|View full text |Cite
|
Sign up to set email alerts
|

Renin inhibition improves metabolic syndrome, and reduces angiotensin II levels and oxidative stress in visceral fat tissues in fructose-fed rats

Abstract: Renin–angiotensin system in visceral fat plays a crucial role in the pathogenesis of metabolic syndrome in fructose-fed rats. However, the effects of renin inhibition on visceral adiposity in metabolic syndrome are not fully investigated. We investigated the effects of renin inhibition on visceral adiposity in fructose-fed rats. Male Wistar–Kyoto rats were divided into 4 groups for 8-week experiments: Group Con (standard chow diet), Group Fru (high-fructose diet; 60% fructose), Group FruA (high-fructose diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
3
19
0
1
Order By: Relevance
“…In the present study, we evaluated renal function and the role of the kidney RAS in animals submitted to high fructose intake from weaning to adulthood by using in vivo and ex vivo methods in this model. Our results showed that high fructose intake determined metabolic and cardiovascular changes, which were consistent with those observed in others studies ( Farah et al, 2006 , 2007 ; Araujo et al, 2016 ; Chou et al, 2017 ; Xu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we evaluated renal function and the role of the kidney RAS in animals submitted to high fructose intake from weaning to adulthood by using in vivo and ex vivo methods in this model. Our results showed that high fructose intake determined metabolic and cardiovascular changes, which were consistent with those observed in others studies ( Farah et al, 2006 , 2007 ; Araujo et al, 2016 ; Chou et al, 2017 ; Xu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, an increase was observed in their visceral fat. These data are consistent with those of other studies using this model in rodents ( Farah et al, 2007 ; De Angelis et al, 2012 ; Chou et al, 2017 ; Xu et al, 2017 ). High fructose diet also induced glucose intolerance and high fasting blood glucose.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The disturbances in the normal redox status of cells cause an increment in reactive oxygen species (ROS) [ 14 ]. Interestingly, MS development in rats fed with fructose [ 15 ] or a high-calorie diet (HCD) [ 16 ] produces an increment in ROS. Therefore, OS could be the link between MS and cognitive disorders [ 13 ].…”
Section: Introductionmentioning
confidence: 99%